HEALTH STATUS AND PROBLEMS OF THE SPECIAL NEEDS CHILDREN - S.Sh. Yafarova; Z.M. Aminova; S.Ya. Volgina ("Paediatrician" Publishers LLC, 2007)
The article highlights the new data on the prevalence and structure of the children's disablement in the Russian federation. Among the causes of the children's disablement, the authors mark dominance of the infectious and somatic diseases, neuropathies, mental diseases and congenital growth anomalies, in particular. They show the role of medical and biological, social and hygienic, medical and organizational and economical factors, defining the health formation and conducing to the children's incapacitation. The researchers characterize the health status of the disabled children in respect of the major indices: physical and neuropsychic growth, psychological personality peculiarities, sickness rate and quality of life. The article depicts many issues, arising within the family of an incapacitated child. Key words: disablement, children, prevalence, structure, causes, health indices.